2022
DOI: 10.1542/peds.2021-055819
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High-Dose DHA Supplementation and Neurodevelopment at 18–22 Months of Preterm Children

Abstract: OBJECTIVES: To determine whether maternal supplementation with high-dose docosahexaenoic acid (DHA) in breastfed, very preterm neonates improves neurodevelopmental outcomes at 18 to 22 months’ corrected age (CA). METHODS: Planned follow-up of a randomized, double-blind, placebo-controlled, multicenter trial to compare neurodevelopmental outcomes in breastfed, preterm neonates born before 29 weeks’ gestational age (GA). Lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…Alternatively, the use of a BPD definition, classified on its severity according to the mode of respiratory support regardless of the need for supplemental oxygen, may be a better outcome associated with early childhood morbidities in modern neonatal respiratory care . Results of this systematic review and meta-analysis did not detect an association between DHA and severe BPD, yet the inverse association of DHA with moderate-to-severe BPD warrants investigation to understand how to balance the potential adverse implications of DHA for BPD with the potential benefits of DHA for neurodevelopment …”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Alternatively, the use of a BPD definition, classified on its severity according to the mode of respiratory support regardless of the need for supplemental oxygen, may be a better outcome associated with early childhood morbidities in modern neonatal respiratory care . Results of this systematic review and meta-analysis did not detect an association between DHA and severe BPD, yet the inverse association of DHA with moderate-to-severe BPD warrants investigation to understand how to balance the potential adverse implications of DHA for BPD with the potential benefits of DHA for neurodevelopment …”
Section: Discussionmentioning
confidence: 76%
“…warrants investigation to understand how to balance the potential adverse implications of DHA for BPD with the potential benefits of DHA for neurodevelopment. [20][21][22] Two trials 19,31 reported an increased risk for BPD after DHA administration in more mature babies, resulting in a higher effect size in this category. However, stratification according to GA was inconclusive, with no subgroup differences found and high evidence of heterogeneity limited the interpretation of results.…”
Section: Sensitivity and Subgroup Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect may have been mediated by BPD. In its secondary analysis, the MOBYDIck trial found that giving DHA supplementation alone to mothers who breastfed their preterm infants is associated with improving the weight velocity in females, only with an opposite impact on males, and these influences are not mediated by BPD [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infants born prematurely are deprived of this in utero accretion of DHA, contributing to their higher risk of developmental delay compared to infants born at term [ 3 , 5 ]. Clinical trials assessing higher doses of DHA in preterm infants have been designed to improve neurodevelopmental outcomes [ 6 , 7 , 8 , 9 , 10 , 11 ]. However, DHA can be a potent anti-inflammatory agent and may have other actions that affect other organ systems.…”
Section: Introductionmentioning
confidence: 99%